1999
DOI: 10.1073/pnas.96.4.1457
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a murine homologue of the inhibitor of apoptosis protein is related to cell proliferation

Abstract: The inhibitor of apoptosis (IAP) proteins form a highly conserved gene family that prevents cell death in response to a variety of stimuli. Herein we describe a newly defined murine IAP, designated Tiap, that proved to be a murine homologue of human survivin based on sequence comparison. TIAP has one baculovirus IAP repeat and lacks a C-terminal RING finger motif. TIAP interacted with the processed form of caspase 3 and inhibited caspase-induced cell death. Histological examinations revealed that TIAP is expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
180
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(195 citation statements)
references
References 31 publications
12
180
0
3
Order By: Relevance
“…It is expressed during human foetal development, but not detectable in normal adult tissues, except in thymus and placenta. Its expression has been showed in several neoplasms, including pancreatic, gastric, colonic, lung, breast, prostatic and bladder cancers, neuroblastomas, and lymphomas (Adida et al, 1998a;Ambrosini et al, 1998;Kawasaki et al, 1998;Lu et al, 1998;Swana et al, 1999;Kobayashi et al, 1999).…”
mentioning
confidence: 99%
“…It is expressed during human foetal development, but not detectable in normal adult tissues, except in thymus and placenta. Its expression has been showed in several neoplasms, including pancreatic, gastric, colonic, lung, breast, prostatic and bladder cancers, neuroblastomas, and lymphomas (Adida et al, 1998a;Ambrosini et al, 1998;Kawasaki et al, 1998;Lu et al, 1998;Swana et al, 1999;Kobayashi et al, 1999).…”
mentioning
confidence: 99%
“…7 Similar to oncofetal antigens, Survivin is strongly expressed in embryonic and fetal organs but is undetectable in most terminally differentiated normal tissues. 7,8,14,23,24 Moreover, genome-wide searches revealed Survivin to be the fourth top 'transcriptome' in various cancers, while remaining low or undetectable in the matched normal tissues. 25 A unique property of Survivin is a sharp cell-cycle-dependent expression at mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis indicated that survivin can partially block activation of caspases and cell death induced by a variety of stimuli, such as Bax, Fas engagement, and etoposide [25]. This appears to be due to its ability to bind to activated caspases [25], [26]. Survivin expression is also closely connected with cell cycle.…”
Section: Iaps and Cell Cycle Controlmentioning
confidence: 99%
“…This is presumably due to failed cytokinesis, the process of separating a cell into two after it has duplicated its genetic material. It has also been shown that the murine homolog of survivin is highly expressed in thymocytes and induced in peripheral T cells upon activation [26], indicating that survivin is also associated with cell cycle progression in untransformed cells. In addition, C. elegans embryos that lack the survivin homologue bir-1 were unable to complete cytokinesis and became multinucleated [30].…”
Section: Iaps and Cell Cycle Controlmentioning
confidence: 99%